Aktivitas Antimalaria Ekstrak Kulit Batang Cempaka Kuning Terhadap Plasmodium Falciparum 3D7 - NI PUTU ARIANTARI; NI LUH RUSTINI; LIDYA TUMEWU; ACHMAD FUAD HAFID; ATY WIDYAWARUYANTI (JURNAL ILMU KEFARMASIAN INDONESIA, 2013)
Cempaka kuning (Michelia champaca) which is belongs to Magnoliaceae family, has been traditionally used for treatment fever. This research was conducted to evaluate antimalarial activity of Cempaka kuning stembark extract against Plasmodium falciparum 3D7 in vitro. Cempaka kuning stembark was extracted with n-hexane, chloroform and methanol yielded n-hexane extract, chloroform extract and methanol extract, followed by antimalarial activity assay of these extracts. Phytochemical screening showed that n-hexane extract contain volatile oil and terpenoids, chloroform extract contain Volatile oil, terpenoids and fiavonoids, then methanol extract contain volatile oil, terpenoids, flavonoids, tannins and glycosides. Result of this study also showed that n-hexane extract, chloroform extract and methanol extract were active against P. alciparum 3D7 in vitro, with an IC50 value of 0.36, 0.24 and 1.00 µg/mL. The findings indicate that Cempaka kuning stembark extracts possess strong antimalarial activity and are prospective to be developed as antimalarial.